ANALYSIS OF SOCIAL SYSTEM BASED ON AGIL CONCEPTS IN CIPTAGELAR COMMUNITY COMMUNITIES - Ruri Susanti; Fauziah Sri Wahyuni (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
Abstract system as a whole so that cultural patterns that have been implemented down and down can be implemented optimally. It can be concluded that the social system in Kampung Gede Kasepuhan Ciptagelar The indigenous people of Kasepuhan Ciptagelar still carry on their ancestral traditions for hundreds of years but can adapt to the times. This research uses a qualitative method with ethnographic studies. The sample of this study used purposive sampling. Based on the analysis of four functions in the form of 1) adaptation (filtering), namely by filtering the modernization adopted with a category that does not harm customs, 2) goal attainment (attainment of goals) as indicated by the philosophy of life as a basic grip with the meaning of life goals to achieve happiness world and the hereafter, 3) integration (integration) of the system in Ciptagelar can make all aspects run well and orderly and are related to each other based on the ties of religious rules (nests), state (nagara), and customs (mokaha), 4) latency (latency or pattern maintenance) carried out by the Ciptagelar community, namely by implementing the can survive based on the identification of the four functions mentioned above. Keywords: indigenous people, Ciptagelar, social system